Interannual Variation in Root Production in Grasslands Affected by Artificially Modified Amount of Rainfall - Karel Fiala; Ivan Tůma; Petr Holub (The Scientific World Journal)
The effect of different amounts of rainfall on the below-ground plant biomass was studied in three grassland ecosystems. Responses of the lowland (dry Festuca grassland), highland (wet Cirsium grassland), and mountain (Nardus grassland) grasslands were studied during five years (2006–2010). A field experiment based on rainout shelters and gravity irrigation simulated three climate scenarios: rainfall reduced by 50% (dry), rainfall increased by 50% (wet), and the natural rainfall of the current growing season (ambient). The interannual variation in root increment and total below-ground biomass reflected the experimentally manipulated amount of precipitation and also the amount of current rainfall of individual years. The effect of year on these below-ground parameters was found significant in all studied grasslands. In comparison with dry Festuca grassland, better adapted to drought, submontane wet Cirsium grassland was more sensitive to the different water inputs forming rather lower amount of below-ground plant matter at reduced precipitation.